2015
DOI: 10.1109/tbme.2015.2395387
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Noninvasive Cardiac Electrophysiological Imaging to Variations in Personalized Anatomical Modeling

Abstract: Objective Noninvasive cardiac electrophysiological (EP) imaging techniques rely on anatomically-detailed heart-torso models derived from high-quality tomographic images of individual subjects. However, anatomical modeling involves variations that lead to unresolved uncertainties in the outcome of EP imaging, bringing questions to the robustness of these methods in clinical practice. In this study, we design a systematic statistical approach to assess the sensitivity of EP imaging methods to the variations in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Precision of the reconstruction of the patient-specific geometry from CT images was studied by Prakosa in [19] and its influence on accurate electrophysiological imaging by Rahimi [20]. In this study specialized image-processing software TomoCon PACS® was used to construct precise patient-specific torso geometries from whole torso CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…Precision of the reconstruction of the patient-specific geometry from CT images was studied by Prakosa in [19] and its influence on accurate electrophysiological imaging by Rahimi [20]. In this study specialized image-processing software TomoCon PACS® was used to construct precise patient-specific torso geometries from whole torso CT scans.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that it was crucial to adapt both the outer shape of the torso model and the position of electrodes according to reality. Yet, it has been also shown that some adapted ventricle-torso standard model were able to get good ECGI results while excluding local geometrical details [20], [21]. Lastly, a recent study uses a generic ventricle-torso model in order to build an EP model training set [15], however the training phase had to be patient-specific as the generic geometry was first registered to every patient geometry.…”
Section: B Reference Anatomy In Ecgimentioning
confidence: 99%
“…Further endeavors have been made to image the electrical activities throughout the three-dimensional (3D) ventricles [11], [24]–[33]. Results from previous studies have demonstrated that the 3D cardiac electrical imaging technique is capable of localizing the 3D ectopic initiation site of different types of arrhythmia [25], [34], [35].…”
Section: Introductionmentioning
confidence: 99%